Cell Cycle Deregulation in Ewing's Sarcoma Pathogenesis. (1st November 2010) - Kowalewski, Ashley A.; Randall, R. Lor; Lessnick, Stephen L.
Abstract : Ewing's sarcoma is a highly aggressive pediatric tumor of bone that usually contains the characteristic chromosomal translocation t(11;22)(q24;q12). This translocation encodes the oncogenic fusion protein EWS/FLI, which acts as an aberrant transcription factor to deregulate target genes necessary for oncogenesis. One key feature of oncogenic transformation is dysregulation of cell cycle control. It is therefore likely that EWS/FLI and other cooperating mutations in Ewing's sarcoma modulate the cell cycle to facilitate tumorigenesis. This paper will summarize current published data associated with deregulation of the cell cycle in Ewing's sarcoma and highlight important questions that remain to be answered.